Reaksi Pasar Modal Sebelum dan Sesudah Peristiwa Pengumuman Presiden dan Wakil Presiden Terpilih Oleh Komisi Pemilihan Umum Tahun 2024: Indonesia - Anugrah, Audito Aji; Wibowo, Reza Septiana (JFAS : Journal of Finance and Accounting Studies, 2024)
Political events such as the 2024 Indonesian Presidential and Vice Presidential election are closely linked to the capital market, drawing significant public attention. This study aims to examine the reaction of the Indonesian capital market to the announcement of the elected President and Vice President by the General Election Commission (KPU) in 2024, measured using abnormal return and Trading Volume Activity (TVA). This research adopts a quantitative approach, utilizing a sample of state-owned enterprises (BUMN) selected based on specific criteria to ensure a more focused sample. The data used include daily closing stock prices of the companies and the Composite Stock Price Index (IHSG), with a 10-day event window period chosen to analyze the impact of the event, as a longer window period could be influenced by other events. The results of this study indicate differences in average abnormal return before and after the announcement of the elected President and Vice President by the General Election Commission in 2024, as well as differences in average Trading Volume Activity (TVA) before and after the announcement.